Pengaruh Penerapan Aplikasi Pengolahan Data Barang Habis Pakai Terhadap Kinerja Pelaporan Pengurus Barang Pengguna Di RSUD HAMS Kisaran - Sinaga, Hommy Dorthy Ellyany; Andriyani, Suci (STIKOM Tunas Bangsa Pematangsiantar, 2019)
This research is to implement an application of single use goods (BHP) data processing which is a computerized system to facilitate of data processing that linked to input, output, inventory card, incoming report, output report, semester and annual recapitulation, and to determine the influence of its implement to the reporting performance. The research method is an explanatory method. By adopting the user acceptance model, this research is formulating the hypothethical that state there is a significance influence of the implemented single use goods (BHP) data processing application to the reporting performance of Pengurus Barang Pengguna. This method is envolving the synthesising the operational variable, data collecting and observation, stating the hypothesis, creating and testing the instrument, distributed the questionnaire to all 7 persons. Based on validity and reliability testing, then the instrument is tested as valid and reliable. The implemented of single used goods (BHP) data processing application is described to be 3 operational variables, ie. the application complexity variable, application use, features and its design variable and application quality variable. The result of hypothesis testing shows that the application complexity and application quality variable are influencing the reporting performance, but the application use, features and its design shows no influence to the reporting performance.